Plausible policy framework to promote sustainable artisanal and small-scale mining. 26th International Mining Congress and Exhibition of Turkey (IMCET2019). April 16 – 19, Antalya-Turkey. - Denhere, R.; T. Zvarivadza, T.; Sengani, F. (2022)
Artisanal and small scale mining (ASM) has emerged as a possible significant contributor to economic growth and development despite its environmental and social challenges. The main aim of this paper is to highlight policy framework that nations can adopt to promote ASM. It acknowledges challenges faced by ASM that ranges from social, environmental, health and safety, marketing to finance. The paper proposes a range of policy framework that the government can adopt to ensure that there is meaningful capturing of rent for economic growth and development. The government can formalize the sector for easy accounting, monitoring and addressing of ASM challenges. The government can also ensure generation of a home grown policy involving all affected stakeholders for the stakeholders to relate to the policy and take ownership of it. Local authorities to be given powers to execute some of the ASM issues since they will be on the ground with the miners. Policy to be of an incentive nature rather than forceful for maximum returns.